The role of electronic fiscal receipting and invoicing system in enhancing tax compliance among smes in Uganda - Sarah Igoda (Uganda Christian University, 2026)
This study examines the influence of digital financial inclusion on financial health in Uganda using data from the FinScope 2023 survey. Financial health is measured as the ability of individuals to meet financial obligations, manage shocks, and maintain financial stability, while digital financial inclusion is captured through access and usage of digital financial services. The study further incorporates demographic characteristics such as income, education, and location to account for heterogeneity across individuals. The analysis employs descriptive statistics, chi-square tests, and regression techniques, including a Linear Probability Model (LPM), to examine the relationship between digital financial inclusion and financial health. The results show that although access to digital infrastructure such as mobile phones and internet services is relatively high, the usage of digital financial services remains uneven, with a significant proportion of individuals not actively engaging with these services. The findings reveal a strong and statistically significant relationship between digital financial inclusion and financial health. Individuals who use digital financial services are significantly more likely to be financially healthy compared to those who do not use such services. The regression results further indicate that engagement in digital financial services reduces the likelihood of poor financial health outcomes, suggesting that usage plays a critical role in improving financial well-being. However, the results also highlight disparities in usage, indicating that not all individuals equally benefit from digital financial inclusion. The study concludes that digital financial inclusion has the potential to improve financial health in Uganda, but its effectiveness depends on active usage rather than access alone. To enhance financial well-being, policies should focus on promoting digital financial literacy, improving affordability and reliability of services, and encouraging inclusive participation in digital financial systems. Keywords: Digital Financial Inclusion, Financial Health, Financial Well-being, FinScope, Uganda
Undergraduate